A New Phenolic Glycoside from the Barks of Cinnamomum cassia - Junfen Zeng; Yongbo Xue; Yongji Lai; Guangmin Yao; Zengwei Luo; Yonghui Zhang; Jinwen Zhang (Molecules, 2014)
A new phenolic glycoside (1), named methyl 2-phenylpropanoate-2-O-β-D-apiofuranosyl-(1→6)-O-β-D–glucopyranoside, was isolated from the barks of Cinnamomum cassia, along with three known phenolic glycosides and four known lignan glycosides. The structure of 1 was elucidated by extensive interpretation of spectroscopic data and chemical method. Selected compounds were evaluated for their immunosuppressive activities against murine lymphocytes. Compounds 1, 2, 6 and 8 exhibited differential inhibition against ConA-induced T cells proliferation.